Does religious faith contribute to the preservation of personal value system in patients with schizophrenia? an empirical research - Dvoinin, Alexey M.; Kopeyko, Grigoriy I.; Borisova, Olga A.; Gedevani, Ekaterina V. (Frontiers in Psychiatry, 2025)
IntroductionAs demonstrated in previous research and clinical observations, the personal value system is subject to disintegration as a consequence of schizophrenia. Patients with schizophrenia are sometimes religious and use religious coping mechanisms. A number of studies emphasize the benefits of positive religious coping as a part of clinical treatment for patients with schizophrenia and schizoaffective disorder. However, the contribution of these patients’ religious faith to the structure and composition of their personal value systems remains unexplored. The present study attempts to answer this question.MethodThe factorial design (2x2) included two conditionally independent variables: mental illness (absent/present) and religious faith (absent/present). We sampled four groups (N = 65) for the study: mentally ill believers of Orthodox Christian faith, mentally ill non-believers, healthy believers, and healthy non-believers. We analyzed the structure and composition of the participants’ personal values employing the following tools underpinned by G. Kelly’s personal construct theory: the triad method, Hinkle’s laddering and repertory grid methods. Correlation and factor analyses were then conducted within each group to find the relationships between the personal values identified. Subsequently, we compared the personal value systems of each group with each other.ResultsThe outcomes of the study reveal that personal values of healthy non-believers are less differentiated than those of healthy Orthodox believers and can be divided into two clusters of meta-values: spiritual and material. Mental illness in non-religious individuals is likely to contribute to disintegration of their personal value systems. Healthy believers have distinctly differentiated and hierarchical personal value systems, while mentally ill believers retain both the general hierarchy and key structures of their personal value systems.DiscussionThe relative stability of the personal value systems of mentally ill believers is explained by their attitude toward illness as a form of trial, which is integrated within the framework of their religious worldview grounded in the Orthodox Christian doctrine. In this way, illness is not regarded as a hindrance to achieving life goals and personal meanings inspired by religion.